Ações de informação no laboratório de aplicações de vídeo digital da Universidade Federal da Paraíba: uma visão a partir do conceito de regime de informação - Bezerra, Emy Pôrto (2018)
This thesis proposes the search and the analysis of elements that allow to observe the actions of information in the Information Regime (Ri) of an academic community (Research Laboratory in Computer Science) that shares an own informational culture. In this way, it aims to evidence the limits and interchanges of this academic "way of life" from the perspective of model of the Ri model evidenced by the researcher Maria Nélida González de Gómez, starting from the assumption that the information culture, shared by the actors within a given social space, contributes to the understanding of its application in a given context. As a methodological procedure, actors, devices, artifacts and information actions were identified in the interface (site) of the Laboratory of Digital Video Applications (LAVID) of the Federal University of Paraíba, pointing out the epistemological limits of this community, a reference laboratory in the development of tools for digital video. We adopt documentary research as a method of data collection, assuming the value of a site as a document that can be analyzed. Thus, we opt for content analysis by choosing as analysis categories the actions of mediation, formative and relational information according to their respective purposes. In the process of investigation the search for indications of how information actions contribute, condition or delineate a Ri, triggering a process of collective intelligence among its social actors, according to the french philosopher Pierre Lévy analysis on the knowledge space in society contemporary art. Among several LAVID projects, we chose three for evaluation as laboratory information actions: Ginga, VLibras and GT-RAP. The first two already completed and the last one still in progress. We adopted as choice criteria the importance, proposal, impact and period that the projects were developed. The evidence observed on the site showed characteristics of the three forms of information action acting simultaneously in the projects surveyed. Thus, we analyze the organization of the LAVID website in tables of observations for analysis of information actions in the Ri in an academic informational culture. These indications were related to the purposes (teleology) of the actions in order to identify similarities and conceptual approaches. There were nuances of intensity among the information actions, confirming the studies of González de Gómez as well as of Harry Collins and Martin Kusch on the existence of "action cascades" or "action trees" in the configuration of Ri. From the analysis of the results we present a suggestion of approximation between the concepts of Ri, collective intelligence and spaces of signification. We observed that even when the information actions in the laboratory coexist in the design and conditioning of their Ri, they are not effectively represented in their interface on the Internet, suggesting an improvement in the communication of information about the laboratory. This achievement will enable its effective use by the academic-scientific community and greater visibility to the external public.We hope to contribute to the understanding of the Ri model as a theoretical and methodological construct for the observation and analysis of information problems of interest in Information Science.